Fundamentals of statistics - Amid, Diego M. (Quezon City, 2005)
The goal of this text is to present statistics in a clear and interesting way. The explanation of statistical methods and concepts is clear and concise. Moreover the style is more user-friendly and easy to understand.
Keywords: Statistics